The mortality of green planthoppers Nephotettix virescens (Homoptera: Cicadellidae) by Metarhizium anisopliae Metchn and Beauveria bassiana (Bals.) Vuill. Issue 2 (July 2021) - Abdullah, T; Aminah, S N; Fatahuddin,; Annisaa, N W
Abstract: The green planthopper Nephotettix virescens Distant (Homoptera: Cicadellidae) is one of the important pests of rice plants in South and Southeast Asia. N. virescens caused damages to rice plants by sucking rice fresh fluid and vector virus of tungro disease. The purpose of research is to determine the effectiveness of two types, entomopathogenic fungi Metarhizium anisopliae and Beauveria bassiana, in suppressing the population level of N. virescens on rice plants. The research activities were held at the Laboratory of Plant Pests and Diseases, Faculty of Agriculture, Hasanuddin University, Makassar, from September 2018 to June 2019. The research used a Factorial, Completely Randomized Design with eight treatments and five replications. Each treatment used ten individual nymphs of N. virescens . The research started from the collection and mass rearing of N. virescens, prepared the rice plants, cultured of M. anisopliae and B. bassiana, application of the entomopathogenic fungi M. anisopliae and B. bassiana . The application of M. anisopliae and B. bassiana on the green planthoppers nymph was showed the average mortality of N. virescens by spraying (89.6%), watering (89.6%), and dipping (89.6%) not significantly. However, the mortality was higher compared to the control (0.50%). Watering treatment used the solution of B. bassiana showed very high average mortality compared dipping used M. anisopliae . The application of M. anisopliae in the spraying and watering treatments showed the average mortality not significantly different compared to the spraying treatment used entomopathogenic B. bassiana .